ON PARAMETRIC ESTIMATION (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we are focused on parametric modeling. To estimate the distribution of the population under study we use the point estimate. For the unknown parameter a of the uniform (continue) distribution U(0,a) we present a better estimator than the sample mean. It will provide a basis for developing efficient estimators when faced with similar problems.